Transfer‐Free, Large‐Scale Growth of High‐Quality Graphene on Insulating Substrate by Physical Contact of Copper Foil. (25th October 2018) - Song, Intek; Park, Yohwan; Cho, Hyeyeon; Choi, Hee Cheul
Abstract: High‐quality, large‐area, single‐layer graphene was directly grown on top of a quartz substrate by a low‐pressure chemical vapor deposition (CVD) process using Cu vapor as a catalyst. In this process, continuous generation and supply of highly concentrated Cu vapor is the key to the growth of large‐scale, high‐quality graphene. It was achieved by direct physical contact, or "touch‐down, " of a Cu foil with an underlying sacrificial SiO2 /Si substrate, and the target quartz substrate was placed on top of the Cu foil, eventually having a quartz/Cu/SiO2 /Si sandwich structure. To establish the reaction mechanism, a test growth was performed without the quartz substrate, which revealed that Cu is diffused through the SiO2 layer of the sacrificial SiO2 /Si substrate to form liquid‐phase Cu‐Si alloy that emits massive Cu vapor. This Cu vapor catalyzes thermal decomposition of supplied CH4 gas.